Effects of electron radiation on commercial power MOSFET with buck converter application - Abubakkar, Sheik Fareed Ookar; Za'bah, Nor Farahidah; Abdullah, Yusof; Ahmad Fauzi, Dhiyauddin; Muridan, Norasmahan; Hasbullah, Nurul Fadzlin (Springer International Publishing AG, 2017)
Microelectronic power converters such as buck and boost converter are required to be tolerant to radiations including electron radiation. This paper examines electron radiation effects on the I–V characteristics of VDMOSFET and its corresponding effects in buck converter. Analysis of the electrical characteristics shows that after irradiation the threshold voltage and drain current for all VDMOSFETs degraded more than two orders of magnitude. The impact of this electrical degradation has been investigated in an application of typical buck converter circuit. The buck converter with n-channel switching transistor shows that after irradiation its output voltage increased with the drain current in the n-channel ZVN4424A VDMOSFET, while the buck converter with p-channel switching transistor shows its output voltage decreased with the drain current in the p-channel ZVP4424A VDMOSFET after irradiation.